An Investigation about Education as Envisioned by Confucius and Its Implications for Contemporary Moral Education - Shaoan, Md Mirajur Rhaman; Jamil, Bushra; Musengamana, Irene; Mahamud, Akash; Chineta, Okoye Maureen; Arif, Muhammad; Namanyane, Tebatso; Akter, Jesmin (Future Science / FSH-PH Publications, 2023)
This study investigates Confucius' views on education and their rel-evance in the 4.0 era. Confucius is known as